Notre-Dame de la Sagesse. - Zundel, Maurice, 1897-1975 (Trésors du Christianisme (Les Éditions du Cerf), 2009)
PROLOGUE-7-I. -- Sagesse et Pauvreté-11-II. -- L'Amour en Croix-29-III. -- La Femme Pauvre-44--IV. -- Hagia Sigê-58-V. -- Stabat Mater-71-VI. -- L'Ostensoir de Jésus-85-VII. -- « Dieu est amour »-105